2019
DOI: 10.1186/s12906-019-2661-y
|View full text |Cite
|
Sign up to set email alerts
|

In vivo assessment of anticoagulant and antiplatelet effects of Syzygium cumini leaves extract in rabbits

Abstract: Background Syzygium cumini (L.) Skeels. is one of the very popular traditionally used medicinal plants with numerous pharmacological activities including antioxidant, hypoglycemic and anti-inflammatory. However, actions of S. cumini on blood coagulation and other parameters of blood were poorly pharmacologically studied. Therefore, aim of this present investigation is to examine the effects of methanolic extract of S. cumini on b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Animals were kept in a standard environment (45-55% humidity and 25°C ± 2°C) with a 12 h light-dark cycle. 33 They were divided into four groups, with 10 rats in each. All administrations were performed orally, and tested solutions were given once daily.…”
Section: In Vivo Acute-and Sub-toxicity Studies Of Cs-agnps Study Animentioning
confidence: 99%
See 1 more Smart Citation
“…Animals were kept in a standard environment (45-55% humidity and 25°C ± 2°C) with a 12 h light-dark cycle. 33 They were divided into four groups, with 10 rats in each. All administrations were performed orally, and tested solutions were given once daily.…”
Section: In Vivo Acute-and Sub-toxicity Studies Of Cs-agnps Study Animentioning
confidence: 99%
“…Different inflammatory biomarkers, including C-reactive proteins, interleukins (IL)-1, IL-2, IL-6, IL-10, and tumor necrosis factor-alpha (TNF-α) were determined by MAGPIX (R&D Systems) in accordance with the manufacturer's instructions provided on commercial assay kits. 33,37 Histopathological Examination Tissues of heart, kidney, and liver were fixed in formalin (10%), and tissues were handled using standard laboratory techniques recommended for histopathological examinations. Tissue cleaning was done using a xylene solution (1%) for 1 h. Then, 3 to 5 µm sections were sliced using a microtome and stained with hematoxyline-eosin (H&E) stain according to the standard protocol for staining.…”
Section: Hematological and Biochemical Analysismentioning
confidence: 99%
“…Myrtaceae with high flavonoids representing the major fraction of phenolic compounds while essential oil of this plant possessed limonene, dipentene and sesquiterpenes of different types as major components [11]. There are several traditional uses of S. cumini such as asthma, ulcers, bronchitis, dysentery, biliousness; diabetes and management of its complications [12].…”
Section: S Cumini Belongs To Familymentioning
confidence: 99%
“…There are several traditional uses of S. cumini such as asthma, ulcers, bronchitis, dysentery, biliousness; diabetes and management of its complications [12]. Experimental studies have shown that S. cumini leaves extract possess anti-nociceptive activity, anti-inflammatory activity, antioxidant effect, antimicrobial potential, antidiabetic and antihyperlipidemic potential [11,13].…”
Section: S Cumini Belongs To Familymentioning
confidence: 99%
See 1 more Smart Citation